Pengaruh Bea Perolehan Hak atas Tanah dan Bangunan (BPHTB), Pajak Bumi dan Bangunan, dan Pajak Resto Terhadap Pendapatan Asli Daerah (PAD) Dalam Perspektif Ekonomi Islam (Studi pada Kabupaten Malang 2017-2019) - Hakim, Arif; Arifiana, Dinda; Rifa'i, Mochamad; Ainulyaqin, Muhammad (Jurnal Ekonomi Syariah Pelita Bangsa, 2020)
Local taxes are an important source of local revenue which is useful for financing regional government administration. BPHTB, PBB, and Resto Tax are local taxes that have an effect in every region, as well as in Malang Regency. The contribution of local taxes in each region varies. This study aims to analyze the influence of BPHTB, PBB, and Resto Tax on PAD Malang Regency in the 2017-2019 period from an Islamic economic perspective. This type of research uses quantitative methods. The results of this study indicate that BPHTB has a positive effect on PAD, while PBB and Resto Tax have a negative effect on PAD in Malang Regency. This research is in line with the opinion of the Islamic figure Abu Yusuf who argues that kharaj (land tax) is allowed with the aim of applying taxes as state revenue to bring benefits to the community.